Fatigue behavior of a wrought Al0.5CoCrCuFeNi two-phase high-entropy alloy. (15th October 2015) - Tang, Zhi; Yuan, Tao; Tsai, Che-Wei; Yeh, Jien-Wei; Lundin, Carl D.; Liaw, Peter K.
Abstract: Fatigue behavior of a cold-rolled two-phase Al0.5 CoCrCuFeNi high-entropy alloy (HEA) was studied. Some specimens were fabricated, using commercial-purity raw materials, while others were manufactured with high-purity components. Scatter in the fatigue life of the commercial-purity samples was found in the stress vs. lifetime plot (S–N curve). However, the high-purity samples showed less scatter, and fatigue life is predictable using fatigue statistics. The fatigue property of the alloy is comparable with and may even outperform many commercial alloys. Fatigue cracking is promoted by shrinkage pores with a size of ∼5 μm, while mechanical nanotwinning was found to be the main deformation mechanism before crack-initiation and during crack propagation by transmission electron microscopy (TEM). Two orientations of dense nanotwins were found at the crack-initiation site, while less-dense nanotwins were found away from the crack initiation site. The nanotwinning behavior resulted in strengthening of the alloy and, consequently, high fatigue strength (383 ± 71 MPa). Moreover, statistical models were applied to predict fatigue life, suggesting that using improved fabrication processes and/or high-purity raw materials may enhance the fatigue behavior and scatter by reducing the number of fabrication microcracks and pores in the test samples.